Pengaruh Model Pembelajaran Levels of Inquiry Disertai Socio-Scientific Issues Terhadap Keterampilan Pemecahan Masalah Siswa Kelas X SMA Materi Ekosistem - Khairunnisa, Faradisa Kirana; Afandi, Afandi; Tenriawaru, Andi Besse (BIOEDUKASI (Jurnal Pendidikan Biologi), 2026)
Problem-solving skills are essential competencies in 21st-century learning, especially in Biology. However, Indonesian students still demonstrate low abilities in solving scientific problems due to passive, teacher-centered learning approaches. This study aims to examine the effect of the Levels of Inquiry learning model integrated with Socio-Scientific Issues (SSI) on students’ problem-solving skills at SMA Negeri 1 Mempawah Hilir and to determine which level of Levels of Inquiry has the most significant impact. This research employed a quantitative approach using a quasi-experimental method with a 3-factor pretest-posttest design, involving three levels: Discovery Learning, Interactive Demonstration, and Inquiry Lesson. A total of 108 students were selected through purposive sampling. The instrument used was an essay test on problem-solving skills, and the data were analyzed using normality and homogeneity tests, one-way ANOVA, and Post Hoc Scheffe tests. The results showed improvement across all groups, with the highest N-Gain in the Inquiry Lesson group (0.83), followed by Interactive Demonstration (0.76), and Discovery Learning (0.67). ANOVA indicated significant differences among the groups (p = 0.001). The Post Hoc Scheffe test revealed significant differences between Discovery Learning and Interactive Demonstration (p = 0.036) and between Discovery Learning and Inquiry Lesson (p < 0.001), but no significant difference between Interactive Demonstration and Inquiry Lesson (p = 0.472). These findings suggest that the Inquiry Lesson integrated with SSI is more effective in enhancing students' problem-solving skills.